2010
DOI: 10.1002/macp.201000023
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Initiated Dispersion Polymerization of Copolymer Microspheres in a Closed System: Poly(MMA‐co‐MAA)

Abstract: A simple closed system is introduced to construct copolymer microspheres with specific surface groups by low‐power UV irradiation. As an example, poly(MMA‐co‐MAA) microspheres with narrow size distribution were prepared by photo‐initiated dispersion polymerization. Sizes and size distributions of the microspheres were closely related to light intensity, composition of dispersion medium and the concentrations of initiators, stabilizers, and monomers. Many carboxyl groups could be moored on the spheres' surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This study set out the effects of reaction conditions, such as stabilizer concentration, monomer concentration, and solvent composition on particle yield and size distribution. An analogous study was reported two years later by Huang et al for the preparation of poly-[(MMA)-co-(MA)] COOH-functionalized microparticles [189]. Irradiation with what was most probably a "black light" tube required a long UV exposure (24 h) to achieve complete conversion.…”
Section: Adaptation To Photoinitiationmentioning
confidence: 60%
“…This study set out the effects of reaction conditions, such as stabilizer concentration, monomer concentration, and solvent composition on particle yield and size distribution. An analogous study was reported two years later by Huang et al for the preparation of poly-[(MMA)-co-(MA)] COOH-functionalized microparticles [189]. Irradiation with what was most probably a "black light" tube required a long UV exposure (24 h) to achieve complete conversion.…”
Section: Adaptation To Photoinitiationmentioning
confidence: 60%
“…PEGDA itself is a good solvent for EY, TEOA and oligomers. With the increase in monomer concentration, the tendency to form larger polymer particles increases due to the longer critical chain length of polymer and thus bigger particles form (54). From the SEM images and DLS data, it can be found that nanogels prepared with 30 wt% monomer concentration have better morphology, and 30 wt% monomer concentration was fixed in the following experiment.…”
Section: Resultsmentioning
confidence: 99%
“…P(St‐Am) microspheres were prepared by UV‐initiated copolymerization of styrene and acrylamide dispersing in an ethanol‐water solution, according to a process reported previously by our group [54,55] . Typically, 1.0 g polyvinylpyrrolidone, 0.2 g 2,2‐azobisisobutyronitrile and 0.5 g acrylamide were dissolved into 40 mL absolute alcohol in a 150 mL conical flask with magnetic stirring and then 10 mL deionized water was added.…”
Section: Methodsmentioning
confidence: 99%